Komunikasi Informasi Edukasi Keluarga Berencana Berbantuan Multimedia untuk Pemilihan Alat Kontrasepsi - Eka Nur Rahayu; C. Asri Budiningsih; B.M.Wara Kushartati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Service quality and Educational Information Communication (IEC) can affect the continuity ofcontraceptive use. The purpose of this study is how the effectiveness of multimedia-assisted KIEFamily Planning (KB) by midwives in assisting the selection of contraceptives for pregnant women.The pre-experimental research design was in the form of a one group pretest-posttest design, namelylooking at the knowledge of pregnant women about family planning before and after IEC and knowingthe selection of contraceptives before and after IEC which was carried out at the Larashati SewonClinic. The sample of this study was 41 pregnant women in the third trimester of pregnancy with thetechnique of taking acidental sampling. The instrument used was a questionnaire. Data analysis usingnonparametric test two samples related test with Wilcoxon. There was a difference in the choice ofcontraceptive before and after being given IEC. There is a difference in the knowledge of pregnantwomen before and after being given IEC. IEC services for family planning by midwives for patientsusing multimedia can increase knowledge, so that it can help pregnant women to choosecontraceptives after childbirth.Keywords: Educational information communication, family planning, contraceptive selection